Demographic Factors Influence on Internal Control Using COSO Components - Magat, Ma. Rofelle (JPAIR Multidisciplinary Research, 2026)
This study analyzed the influence of demographic factors on employees’ perceptions of internal control effectiveness in selected commercial banks in Metro Manila. Anchored on the COSO Internal Control–Integrated Framework (2013), the research focused on five components: control environment, risk assessment, control activities, information and communication, and monitoring. A quantitative descriptive design was employed, utilizing a structured survey instrument administered to employees across organizational levels. Statistical tools, such as group comparison tests and ordinal logistic regression, were used to analyze the data. Findings revealed that civil status and length of service were significant predictors of how employees evaluate internal controls, with married and longer-tenured employees tending to be more critical. Age and job position also showed differences in perceptions, while sex and educational attainment did not yield significant predictive effects. The results highlight that demographic diversity shapes perceptions of governance and compliance, though organizational culture and system design may exert greater overall influence. The study concludes that tailoring governance initiatives to demographic profiles can enhance internal control effectiveness. Recommendations include strengthening governance structures, refining Bangko Sentral ng Pilipinas [BSP] regulatory support, and expanding future research to rural, cooperative, and digital banks. By addressing this research gap, the study contributes to both academic literature and practical banking governance, while aligning with the United Nations Sustainable Development Goals (SDG 8, SDG 16, and SDG 5).